Digital Keywords: printing, aesthetics, visual creativity: الطباعة الرقمية وجمالية الإبداع البصري - Maha Abdul Rahman Abdul Razzaq Al Hashimi (Journal of engineering sciences and information technology, 2018)
The aesthetic of digital printing is one of the most important developments. Note that the importance of digital printing technology in terms of feeling when used, through designs. The aesthetic of digital printing is one of the most important variables. Which vary according to the sense of effectiveness of the print presentation from one way to another or according to technical and psychological differences between them. The requirements for this feature vary depending on the type of final use of the product. The studies have shown that there are elements that interfere with the printing media and the techniques used which is represented in printing using the computer through techniques and three-dimensional according to scientific algorithms that is taken into account the technical aspects of the subject of printing or may be taken into account the art of the use of colors and the strength of the attraction (economic, technical and social links to the work of print art), which varies according to the age of the consumer, which in turn provides comfort and aesthetic to the consumer. On the aesthetic technical features, the role of technical techniques (visual), which is reflected in the experience and design of the product in digital technical printing.